Children Education in the Book of Tarbiyatul Aulad Fil Islam Based on Abdullah Nashih Ulwan’s and Philosophy of Education Perspectives - Tafiudin, Muhammad (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
This study aims to explore the concept of children's education as presented in the Book of Tarbiyatul Aulad Fil Islam by Abdullah Nashih Ulwan. The research delves into the fundamental principles of children's education according to Ulwan, the objectives of this educational process, as well as the materials and methods he advocates. Employing a qualitative approach, this study relies on library research as its research type, with data collection conducted through meticulous documentation methods. The analysis of gathered data follows a qualitative approach and adopts a descriptive method. The findings reveal that Abdullah Nashih Ulwan's concept of children's education encompasses a foundation in Basic Education, emphasizing the principles of faith (Akidah) and spiritual connection, while maintaining a balance between individual and community needs. The materials for children's education include nurturing a virtuous character, upholding the rights of others, and employing various methods such as education by example, guidance, supervision, and disciplinary measures.